Sustainable Tourism and Public Opinion: Examining the Language Surrounding the Closure of Uluru to Climbers - Tombleson, Bridget; Wolf, Katharina (Springer, 2022)
The decision to cease the climbing of one of Australia’s major tourist attractions, the UNESCO World Heritage site Uluru, on 26th October 2019, has attracted much controversy, debate and worldwide attention.